2009
DOI: 10.1086/605534
|View full text |Cite
|
Sign up to set email alerts
|

Human Paragonimiasis in North America following Ingestion of Raw Crayfish

Abstract: Paragonimiasis (human infections with the lung fluke Paragonimus westermani) is an important public health problem in parts of Southeast Asia and China. Paragonamiasis has rarely been reported from North America as a zoonosis caused by Paragonimus kellicotti. Paragonimus species have complex life cycles that require 2 intermediate hosts, namely, snails and crustaceans (ie, crabs or crayfish). Humans acquire P. kellicotti when they consume infected raw crayfish. Humans with paragonimiasis usually present with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
69
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 28 publications
0
69
0
2
Order By: Relevance
“…In the United States, P. kellicotti is found living in a broad range of mammalian hosts mainly in the midwestern and southern United States within the Mississippi River Basin. Most cases of autochthonous paragonimiasis in the United States caused by native P. kellicotti flukes are transmitted by the ingestion of raw or undercooked crayfish, the preferred crustacean intermediate hosts for P. kellicotti (1)(2)(3). The U.S. regional distribution of P. kellicotticaused paragonimiasis cases is depicted in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, P. kellicotti is found living in a broad range of mammalian hosts mainly in the midwestern and southern United States within the Mississippi River Basin. Most cases of autochthonous paragonimiasis in the United States caused by native P. kellicotti flukes are transmitted by the ingestion of raw or undercooked crayfish, the preferred crustacean intermediate hosts for P. kellicotti (1)(2)(3). The U.S. regional distribution of P. kellicotticaused paragonimiasis cases is depicted in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Within Paragonimidae, species from Paragonimus, highly evolved parasites with a complex life cycle that involves at least three different hosts, i.e., snails, crustaceans, and mammals, are known to use crayfish species, including P. clarkii, as intermediate hosts (Sogandares-Bernal, 1965); the adults of Paragonimus reside and mate in the lungs of a variety of mammalian hosts, wild and domestic animals, as well as humans, causing a disease named paragonimiasis (Lane et al, 2009;Procop, 2009).…”
Section: Trophic Ecologymentioning
confidence: 99%
“…Previous case reports showed that months or years may pass between the onset of the illness and parasitological diagnosis. 3,4 Diagnosis was often delayed for many months after the onset of symptoms, and patients often failed therapeutic trials of antibiotics and/or steroids before proper diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%